2021
DOI: 10.3389/fphar.2021.599180
|View full text |Cite
|
Sign up to set email alerts
|

Mahuang Decoction Antagonizes Acute Liver Failure via Modulating Tricarboxylic Acid Cycle and Amino Acids Metabolism

Abstract: Acute liver failure (ALF) is a serious clinical disorder with high fatality rates. Mahuang decoction (MHD), a well-known traditional Chinese medicine, has multiple pharmacological effects, such as anti-inflammation, anti-allergy, anti-asthma, and anti-hyperglycemia. In this study, we investigated the protective effect of MHD against ALF. In the lipopolysaccharide and D-galactosamine (LPS/D-GalN)-induced ALF mouse model, the elevated activities of the serum alanine and aspartate transaminases as well as the liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 46 publications
(55 reference statements)
1
6
0
Order By: Relevance
“…The enrichment analysis of the hub metabolites indicated their involvement in nicotinate and nicotinamide metabolism, retinol metabolism, “alanine, aspartate, and glutamate metabolism,” and tryptophan metabolism. A previous study found that nicotinate and nicotinamide metabolism was impaired in acute liver failure and could be reversed by mahuang decoction [ 45 ], which similarly corroborates with our present findings. Altered retinol metabolism has been incriminated in diverse liver conditions such as hepatic fibrosis and nonalcoholic fatty liver disease [ 46 ]; here, we also found similar results.…”
Section: Discussionsupporting
confidence: 93%
“…The enrichment analysis of the hub metabolites indicated their involvement in nicotinate and nicotinamide metabolism, retinol metabolism, “alanine, aspartate, and glutamate metabolism,” and tryptophan metabolism. A previous study found that nicotinate and nicotinamide metabolism was impaired in acute liver failure and could be reversed by mahuang decoction [ 45 ], which similarly corroborates with our present findings. Altered retinol metabolism has been incriminated in diverse liver conditions such as hepatic fibrosis and nonalcoholic fatty liver disease [ 46 ]; here, we also found similar results.…”
Section: Discussionsupporting
confidence: 93%
“…Pathway enrichment analysis of differential metabolites and differential lipid molecules revealed that several metabolic pathways, including drug metabolism-other enzymes, niacin and nicotinamide metabolism, tyrosine metabolism, tryptophan metabolism, ferroptosis, and unsaturated fatty acid biosynthesis pathways ( Tables 3 , 5 ), are related to the occurrence of ATB-DILI. Mahuang Decoction can significantly protect against DILI by regulating the metabolic pathways of niacin and nicotinamide and the metabolism of tryptophan ( Liao et al, 2021 ). Tyrosine and tryptophan biosynthesis and phenylalanine and tyrosine metabolism were found to be significantly associated with DILI in a hydrazine-induced rat liver injury model ( An et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative damage induced by mitochondrial ROS production is an important molecular basis for various pathophysiological conditions, including aging and cancer ( 34 ). It was found that the metabolism of fatty acids and amino acids is an important pathway of the tricarboxylic acid cycle ( 35 ). Our results revealed that fatty acid, bile acid, and amino acid metabolites and metabolic pathways were reduced in response to Cd 2+ intervention, and the differential metabolites and metabolic pathways were more affected in the High-dose group.…”
Section: Discussionmentioning
confidence: 99%